Iron based catalysts from novel low-cost organic precursors for enhanced oxygen reduction reaction in neutral media microbial fuel cells. Issue 7 (18th May 2016) - Santoro, Carlo; Serov, Alexey; Stariha, Lydia; Kodali, Mounika; Gordon, Jonathan; Babanova, Sofia; Bretschger, Orianna; Artyushkova, Kateryna; Atanassov, Plamen
Abstract : Fe-based catalysts based on ricobendazole and niclosamide showed higher performance compared to Pt (20–25%) and AC (90–99%) and more durability in long terms operations. Abstract : Two iron-based platinum group metal-free catalysts for the oxygen reduction reaction (ORR) were synthesized from novel and low cost organic precursors named niclosamide and ricobendazole. These catalysts have been characterized, incorporated in a gas diffusional electrode and tested in "clean" conditions as well as in operating microbial fuel cell (MFC) for 32 days. Both catalysts demonstrated unprecedented performance yielding a power density 25% higher than that of platinum (Pt) and roughly 100% higher than activated carbon (AC) used as a control. Durability tests were performed and showed that Pt-based cathodes lost their activity within the first week of operation, reaching the level of the supporting AC-based electrode. Fe–ricobendazole, however, demonstrated the highest performance during the long-term study with a power density of 195 ± 7 μW cm −2 (day 2) that slightly decreased to 186 ± 9 μW cm −2 at day 29. Fe–niclosamide also outperformed Pt and AC but the power density roughly decreased with 20% for the 32 days of the study. Accelerated poisoning test using S 2− as pollutant showed high losses in activity for Pt. Fe–niclosamide suffered higher losses compared to Fe–ricobendazole. Importantly, Fe–ricobendazole represents a 55-fold cost reduction compared to platinum.